Cellular Recycling Gone Wrong: The Role of Dysregulated Autophagy and Hyperactive mTORC1 in the Pathogenesis of Sarcoidosis - Adouli, Jennifer; Aaron Fried; Rachel Swier; Andrew Ghio; Irina Petrache; Stephen Tilley (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aims: Autophagy is a highly regulated, complex intracellular recycling process that is vital to maintaining cellular homeostasis in response to diverse conditions and stressors. Despite the presence of robust regulatory pathways, the intricate and multi-step nature of autophagy creates opportunity for dysregulation. Errors in autophagy have been implicated in the development of a broad range of clinical pathologies including granulomatous disease. Specifically, activation of the mTORC1 pathway has been identified as a key negative regulator of autophagic flux, prompting the study of dysregulated mTORC1 signaling in the pathogenesis of sarcoidosis. Our review: We conducted a thorough search of the extant literature to identify the regulatory pathways of autophagy, and more specifically the implication of upregulated mTORC1 pathways in the pathogenesis of sarcoidosis. We review data showing spontaneous granuloma formation in animal models with upregulate mTORC1 signaling, human genetic studies showing mutation in autophagy genes in sarcoidosis patients, and clinical data showing that targeting autophagy regulatory molecules like mTORC1 may provide new therapeutic approaches for sarcoidosis. Conclusions: Given the incomplete understanding of sarcoidosis pathogenesis and the toxicities of current treatments, a more complete understanding of sarcoidosis pathogenesis is crucial for the development of more effective and safer therapies. In this review, we propose a strong molecular pathway driving sarcoidosis pathogenesis at which autophagy is at the center. A more complete understanding of autophagy and its regulatory molecules, like mTORC1, may provide a window into new therapeutic approaches for sarcoidosis.